Straight Punch Technique on Sasana Lipang Bajeng Boxing Athletes - Latuheru, Ricardo Valentino; Hanafi, Suriah (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research is a descriptive study, which aims to determine jab and straight punch techniques in Sasana Lipang Bajeng boxing athletes. Data retrieval is the skill level of jab and straight punches. Populasi is a boxing athlete from Sasana Lipang Bajeng while the determination of samples using the total sampling method is the number of samples in the study equal to the existing population of 15 athletes. The results showed that the straight hitting technique of 15 athletes, was categorized as good as 1 athlete or (6.67%), the good category as many as 10 athletes or (66.67%), the medium category as many as 4 athletes or (26.67%), and for the less and less categories there was nothing. Thus, it can be concluded that the straight punch technique of Sasana Lipang Bajeng boxing athletes is in the Good category.